An Activity Model to Enhance Public Mind Through Active Learning for Students of Chiang Mai Rajabhat University - chatyalak, paphat; Plewthong, Chutharat (Journal of Graduate Research, 2020)
The objectives of this study were to construct an activity model to enhance public mind through active learning for students of Chiang Mai Rajabhat University, and to investigate the implementation results of the model. The sample group consisted of 40 regular program students of Chiang Mai Rajabhat University obtained through the purposive sampling method. The research instruments were composed of an activity model to enhance public mind through active learning and a public mind test. The data were analyzed for mean, standard deviation, and the Wilcoxon t-test (The Wilcoxon Matched Pairs Signed-Ranks Test) was utilized to test the research hypotheses. The research results revealed that the activity model to enhance public mind through active learning consisted of fundamental principles, the rationale, the objectives, the experiential learning-based activities with the E-R-C-A steps, and the project-based Learning with the D-P-D-R-P steps. The propriety of the measurement and evaluation was at the highest level (µ=4.50, s=0.33). The level of the public mind of the participating students was significantly higher after participating in the activities at the .05 level.